Designing a Decision Support System for Educational Resource Allocation - Lusy Tunik Muharlisiani; Widyatmike Gede Mulawarman; S Suwarni; Usanto S; Berman Hutahaean; Robbi Rahim (AL-ISHLAH: Jurnal Pendidikan, 2023)
The effective allocation of educational resources is crucial for enhancing the quality of education. This study explores the development and application of a decision support system (DSS) using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. Various entities are evaluated based on a set of critical criteria. Using the TOPSIS approach, entities were systematically ranked, offering a clear directive for optimal resource allocation. This study provides a significant tool for resource management, offering a transparent, objective, and data-driven process. However, DSS should complement other qualitative and contextual considerations in the decision-making process. Future research directions include the integration of temporal data, broadening the set of criteria, and the inclusion of machine learning for dynamic decision-making. Ultimately, this study underscores the value of systematic and data-driven processes in resource allocation, contributing to the improvement of the quality of education